2020
DOI: 10.29245/2578-3025/2020/2.1189
|View full text |Cite
|
Sign up to set email alerts
|

Role of Monoamine Oxidase A (MAO-A) in Cardiac Aging

Abstract: Among different sources that contribute in the global oxidative stress, the vast majority of cellular reactive oxygen species (ROS) originate from mitochondrial compartments. Recently, monoamine oxidases (MAOs) are identified as a prominent source of ROS. Monoamine oxidases are localized in the outer membrane of mitochondria and exist as two different isoforms, MAO-A and MAO-B. MAOs are mitochondrial flavoenzymes responsible for oxidative deamination of biogenic amines and during this process, H 2 O 2 and alde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…It has also been reported that MAO-A is involved in reactive oxygen species (ROS) generation in alternatively activated monocytes/macrophages (84). The high production of ROS has been implicated in the pathogenesis of several human diseases involving cancer, as well neurodegenerative, cardiovascular, inflammation-and ageing-related disorders (85)(86)(87). The downregulation of MAO-A has been observed in various types of cancer cells, such as cholangiocarcinoma, esophageal squamous cell carcinoma and hepatocellular carcinoma (88,89).…”
Section: Role Of Hat and Hdac In Regulating Anti-inflammatory Gene Expressionmentioning
confidence: 99%
“…It has also been reported that MAO-A is involved in reactive oxygen species (ROS) generation in alternatively activated monocytes/macrophages (84). The high production of ROS has been implicated in the pathogenesis of several human diseases involving cancer, as well neurodegenerative, cardiovascular, inflammation-and ageing-related disorders (85)(86)(87). The downregulation of MAO-A has been observed in various types of cancer cells, such as cholangiocarcinoma, esophageal squamous cell carcinoma and hepatocellular carcinoma (88,89).…”
Section: Role Of Hat and Hdac In Regulating Anti-inflammatory Gene Expressionmentioning
confidence: 99%